Urgensi Labelisasi Halal Produk Obat Over-the-Counter dalam Upaya Perlindungan Konsumen - Melinda Nurdin; Muthia Sakti (Jurnal USM Law Review)
This article desires to explain the urgency of halal labeling of over-the-counter (OTC) medicines products to protect consumers in Indonesia and analyze the legal aftereffect for business actors if not carry out halal labeling. The Muslim population dominates most of the total population in Indonesia, likely at 86,7%.. For this reason, the halal status and guarantee of a product is an issue that cannot be underestimated, in which case a halal certificate is believed to be the best option. However, apart from halal certificates, halal labels also play an important role, especially for OTC medicines products which are still found not to have halal labels on the market. The method is normative legal research with regulatory analysis. Research that focuses on the aspect of the urgency of halal labeling as the second stage of halal certification for OTC medicine products is an element of novelty. This article finds that the basis for the urgency of halal labeling on OTC medicine products was found because it's mandatory and is intended as an effort to protect consumers, especially regarding the rights to safety, comfort, and information. Apart from that, it's also because the halal label is meaningful for business actors and the state from an economic perspective and eliminates the perception of emergency law on OTC medicines circulating in society. The legal aftereffect for business actors in case they don’t carry out halal labeling for OTC medicines products is that they may be subject to administrative sanctions determined by BPJPH.